Adaptive Policies for Reducing Inequalities in the Social Determinants of Health - Gemma Carey; Brad Crammond; Eleanor Malbon; Nic Carey (Kerman University of Medical Sciences, 2015)
Inequalities in the social determinants of health (SDH), which drive avoidable health disparities between different individuals or groups, is a major concern for a number of international organisations, including the World Health Organization (WHO). Despite this, the pathways to changing inequalities in the SDH remain elusive. The methodologies and concepts within system science are now viewed as important domains of knowledge, ideas and skills for tackling issues of inequality, which are increasingly understood as emergent properties of complex systems. In this paper, we introduce and expand the concept of adaptive policies to reduce inequalities in the distribution of the SDH. The concept of adaptive policy for health equity was developed through reviewing the literature on learning and adaptive policies. Using a series of illustrative examples from education and poverty alleviation, which have their basis in real world policies, we demonstrate how an adaptive policy approach is more suited to the management of the emergent properties of inequalities in the SDH than traditional policy approaches. This is because they are better placed to handle future uncertainties. Our intention is that these examples are illustrative, rather than prescriptive, and serve to create a conversation regarding appropriate adaptive policies for progressing policy action on the SDH.